Typical Characteristics of Lexical Meanings - Oygul Makhmudova (Zien Journals, 2023)
The emergence of derived word meanings is of great importance in the formation of lexical meaning types. However, in linguistics, lexical meanings are not classified into universally recognized types. V. V. Vinogradov tried it first, then K. A. Levkovskaya, I. V. Arnold, N. M. Shansky, D. N. Shmelev, N. I. Fomina recorded its classification in their works, sometimes without changes, sometimes with changes. However, their opinion was not the same regarding the definition of lexical meaning types. This has been noted by some linguists. The Uzbek linguist Sh.Rakhmatullayev also touched on the types of lexical meaning in his work on lexicology, but he was also limited by the existing tradition.
Keywords: lexical meaning; expression of meaning; collocation; artificial meaning; related meaning